A redescription of the carinate pillsnail, Euchemotrema hubrichti (Pilsbry, 1940) (Pulmonata: Polygyridae), with notes on habitat and genetics - Anderson, Frank E.; Smith, David A. (Zootaxa, 2005)
Euchemotrema hubrichti (Pilsbry, 1940) was initially described as Stenotrema hubrichti by Pilsbry (1940). The species was known only from shell material, and it was originally thought to be extinct. Live specimens have since been found, but the soft-part anatomy, radula and jaws of E. hubrichti have never been described. This species is of substantial conservation concern, primarily due to our lack of knowledge about the species and its highly restricted distribution. We redescribe E. hubrichti based on material freshly collected from the type locality. Euchemotrema hubrichti is found at several sites in the Larue–Pine Hills Research Natural Area in Union County, Illinois, U.S.A., and is often abundant under loose slabs on the tops of relatively dry limestone outcrops. The shell of E. hubrichti differs from those of E. fraternum (Say, 1824) by its acute keel and low number of whorls. The genitalia of E. hubrichti are similar to those of S. stenotrema (Pfeiffer, 1842), but show a diagnostic penile inflation and lumenal twisting of the free oviduct. Partial mitochondrial cytochrome c oxidase subunit I nucleotide sequences generated from four E. hubrichti individuals are identical, and show high similarity to available stylommatophoran sequences.